Metode Qiyas Badan Syariah Nasional Fatwa dan Permasalahan Ekonomi Islam Kontemporer - Nuraeni, Neni; Abdullah, Muhammad Najib (Jurnal Hukum Islam, 2024)
The Qiyas method in the formation of fatwas of the National Sharia Board-Indonesian Ulema Council aims to provide legal solutions to contemporary Sharia economic problems that have no precedent in classical Islamic legal texts. Therefore, the Qiyas method must be relevant and responsive to the development of sharia financial institutions. This study discusses the application of the qiyas method in the process of making fatwas of the National Sharia Board-Indonesian Ulema Council, and its implications for contemporary Sharia economic problems. The research method uses normative juridical with a conceptual and philosophical approach. The sources of legal materials are contemporary fatwas from the National Sharia Board, such as Sukuk, Sharia insurance, istishna', Sharia credit cards and others that are relevant. The data collection technique uses documentation studies. The research findings show that the application of the qiyas method in Sharia economic fatwas on sukuk, murabahah financing, Sharia insurance, istishna' financing, and Sharia credit cards shows flexibility towards the development and innovation of contemporary Sharia finance. The qiyas method has implications for maintaining the conformity between contemporary financial products and Sharia principles, increasing the flexibility and dynamics of Sharia economic law, providing legal certainty and standardization in Sharia financial institutions, assisting innovation in Sharia financial products and services, reducing the potential for legal ambiguity and increasing public understanding of sharia economic law.